2015
DOI: 10.1590/0001-3765201520140712
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of Anti-Scrapie Trimethoxychalcones and Oxadiazoles

Abstract: An altered form of the cellular prion protein, the PrP Sc or PrP Res, is implicated in the occurrence of the still untreatable transmissible spongiform encephalopathies. We have previously synthesized and characterized aromatic compounds that inhibit protease-resistant prion protein (PrP Res ) accumulation in scrapie-infected cells. These compounds belong to different chemical classes, including acylhydrazones, chalcones and oxadiazoles. Some of the active compounds were non-toxic to neuroblastoma cells in cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The six trimethoxychalcones compounds tested did not show any significant toxicity in all organs/glands of experimental animals (Figueiredo et al, 2015). In contrast, this study showed toxicity effect of DPP on the liver and kidneys (Figure 5 and 6).…”
mentioning
confidence: 50%
“…The six trimethoxychalcones compounds tested did not show any significant toxicity in all organs/glands of experimental animals (Figueiredo et al, 2015). In contrast, this study showed toxicity effect of DPP on the liver and kidneys (Figure 5 and 6).…”
mentioning
confidence: 50%
“…In a previous study, we analyzed a panel consisting of over 200 aromatic compounds and found four chalcones (compounds J1, J8, J20, and J35) and two oxadiazoles (compounds Y13 and Y17) able to decrease PrP Res levels by at least 50% in RML strain scrapie-infected N2a (ScN2a-RML) cells with 50% effective concentrations up to 10 M. Additionally, these compounds were devoid of toxicity for ScN2a cells and were predicted to have an adequate drug-like profile (23). The acute toxicity of these substances was evaluated in vivo, and we found that single oral administration (300 mg/kg of body weight) or repeated intraperitoneal administration (10 mg/kg 3 times a week for 4 weeks) did not cause toxic effects in mice (25). Based on these findings, in the study described here we analyzed by the RT-QuIC assay the efficacies of four of these compounds (compounds J1, J8, J20, and Y17, the structures of which are shown in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…This construction lacks the N-terminal region, which comprises a critical binding site for PrP Sc and is therefore crucial for prion propagation. Mice expressing PrP C with a deletion in this region (a deletion from residues 23 to 31 [Δ [23][24][25][26][27][28][29][30][31] ]) exhibit resistance to prion infection, as evidenced by elongated incubation times and delayed accumulation of PrP Sc (45). PrP interaction with ligands putatively associated with its physiological function can also be mediated by this region (reviewed in references 17 and 46).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations